PENGARUH ASIMETRI INFORMASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA LEMBAGA PERKREDITAN DESA SE-KECAMATAN TEGALLALANG - I Gede Apriana; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2021)
This study aims to provide empirical evidence regarding the significance of the effect of information asymmetry and adherence to accounting rules on the tendency of accounting fraud at Village Credit Institutions in Tegallalang District. The sample used was 108 respondents. The sample collection method used was purposive sampling technique. The data used are primary data obtained by distributing questionnaires to respondents. The analysis technique used is descriptive statistics, non-response bias test, validity test, reliability test, classic assumption test, multiple regression analysis, coefficient of determination (R2), F test, t test. The results of the research prove that: (1) Information asymmetry has a positive effect on the tendency of accounting fraud, with a regression coefficient value of 0.410 and a significance value (Sig.) Of 0.007 less than 0.05. This shows that the increase in information asymmetry has an impact on the increasing tendency of accounting fraud. (2) Adherence to accounting rules has a negative effect on the tendency of accounting fraud, with a regression coefficient value of -0.422 and a significance value (Sig.) Of 0.000 less than 0.05. This shows that an increase in the compliance of accounting rules has an impact on the decrease in the tendency of accounting fraud.